An Uncertain Risk: The World Health Organization's Account of H1N1. Issue 3 (28th July 2014) - Abeysinghe, Sudeepa
Argument Scientific uncertainty is fundamental to the management of contemporary global risks. In 2009, the World Health Organization (WHO) declared the start of the H1N1 Influenza Pandemic. This declaration signified the risk posed by the spread of the H1N1 virus, and in turn precipitated a range of actions by global public health actors. This article analyzes the WHO's public representation of risk and examines the centrality of scientific uncertainty in the case of H1N1. It argues that the WHO's risk narrative reflected the context of scientific uncertainty in which it was working. The WHO argued that it was attempting to remain faithful to the scientific evidence, and the uncertain nature of the threat. However, as a result, the WHO's public risk narrative was neither consistent nor socially robust, leading to the eventual contestation of the WHO's position by other global public health actors, most notably the Council of Europe. This illustrates both the significance of scientific uncertainty in the investigation of risk, and the difficulty for risk managing institutions in effectively acting in the face of this uncertainty.